A community-based study to estimate the contraceptive prevalence rate among the women of reproductive age group in rural North India - Thakur, Anita; Gupta, Anmol K.; Chauhan, Tripti; Chauhan, Nidhi (International Journal Of Community Medicine And Public Health, 2020)
Background: The utilization of family planning services has improved over the decade, but still the SDG’s health target to ensure universal access to sexual and reproductive health care services is yet to be achieved. Methods: A cross-sectional study was undertaken in the rural field practice area of Department of Community Medicine, Indira Gandhi Medical College, Shimla, Himachal Pradesh, India, from September to December 2019, with sample size of 316. The eligible participants were administered a predesigned, pretested, semi-structured and anonymous interview schedule after taking consent. Results: The mean age of the participants was 30.2±6.1 years. The modern contraceptive prevalence rate (mCPR) was found to be 67.7% among women of reproductive age group 15-49 years. Male condom 36%, followed by female sterilization 30% were the most common methods preferred. Conclusions: Besides male condoms and female sterilisation, other methods of contraception were adopted by meagre number of women. Though, the unmet need for family planning was lesser in this study, still, efforts are needed to plunge it, for ameliorating the contraceptive prevalence rate. Also, the availability of basket of contraceptive choices in government sector need sheer assiduity.